NICOTINE EXPOSURE DURING BREASTFEEDING ALTERS CARDIAC PARAMETERS IN MALE AND FEMALE OFFSPRING - Carla Carolina Rodrigues da Silveira; Marcos Divino Ferreira-Junior; Keilah Valéria Naves Cavalcante; Ariel Penha Carvalho da Mota; Patrícia Cristina Lisbôa da Silva; Rodrigo Mello Gomes (Arquivos do Mudi, 2023)
Nicotine is one of the main psychoactive and toxic substances found in tobacco and itsexposure during the postnatal period can cause several damages to the health of the childduring intrauterine development and in adult life. The aim of this study was to evaluate theeffect of maternal postnatal nicotine exposure on cardiac parameters in adult rat offspring.Weight monitoring, echocardiography and organ collections were performed. In conclusion,offspring from mothers exposed to nicotine develops cardiac hypertrophy, further maleoffspring were more affected.